A variação entre textos argumentativos e o material didático de inglês: aplicações da análise multidimensional e do Corpus Internacional de Aprendizes de Inglês (ICLE) - Lúcio, Denise Delegá (2013)
This thesis aims to check the way how argumentative texts produced by English learners vary and, by means of this knowledge, suggest procedures for developing activities for English teaching material. The research resorts to the theoretical framework of Corpus Linguistics, Learner Corpus Linguistics, and Multidimensional Analysis. Our study corpora were the International Corpus of Learner English (ICLE), the Brazilian International Corpus of Learner English (BrICLE), and the Louvain Corpus of Native English Essays (LOCNESS). In the first phase of this research, we checked the way how variation in learner s essays was distributed along the dimensions of English variation proposed by Biber (1988). In the second phase, we identified the specific variation dimensions in leaner s essays, something which resulted in 4 dimensions of variation: dimension 1 literate writing versus narrativelike and oral-like writing; dimension 2 description-driven writing versus action-driven writing; dimension 3 writing focused on thought and report; and dimension 4 qualifying writing. In the third phase, we addressed the linguistic characteristics observed in the dimension literate writing versus narrative-like and oral-like writing to find contents for the teaching activities about variation in texts. In addition to the suggested activities, we present the procedures needed to use results from researches like this for producing language teaching materials